2021
DOI: 10.1177/11206721211035615
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal structural changes and choroidal vascularity index in patients with systemic hypertension

Abstract: Purpose: To assess the impact of systemic hypertension on the choroidal structure and choroidal vascularity index (CVI). Methods: This prospective cross-sectional study comprised 50 eyes of 50 treatment-naive hypertensive patients and 50 eyes of 50 healthy subjects. Choroidal thickness (CT) was measured in the subfoveal region, 1500 µm nasal to the fovea, and 1500 µm temporal to the fovea. Binarization of the enhanced depth-optical coherence tomography images was performed with Image-J software. The CT, choroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The electronic database search identified 1011 studies. After screening, a total of six studies 21 26 met the inclusion criteria. Individual study characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The electronic database search identified 1011 studies. After screening, a total of six studies 21 26 met the inclusion criteria. Individual study characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The quality assessment scores of the NOS are shown in Table 1 . Three studies 23 – 25 included in the analyses were of high quality, featuring a score equal or higher of seven and the remaining three 21 , 22 , 26 were of medium quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings could prove that CVI, regardless of the area of assessment, is a stable and reliable indicator of choroidal changes in the presence of DM. However, Aşıkgarip et al found that HBP in treatment-naive patients impacts the SF-CT, LA and CVI and reported a negative correlation between choroidal parameters and HBP [ 55 ]. In our study, both SF-CT and CVI were not associated with the presence of HBP.…”
Section: Discussionmentioning
confidence: 99%